Exploring Online Interaction through Connectivism: A Case Study of Universiti Teknologi MARA (UiTM) Learners - Ahmad Buhari, Turisiana; Azizul Hassan, Aini Faridah (Asian Social Work Journal, 2025)
Spurred by the COVID-19 pandemic, learning dynamics have changed as learners are no longer confined to a traditional education setting. Considering the Connectivism learning theory, this study explores English as a Second Language (ESL) learners’ perceptions of online learning, focusing on online interaction and Connectivism. The Connectivism learning theory provides a framework for understanding learning in the digital age, whereby the learning process happens when individuals connect and interact with information, technology, and other people virtually. A quantitative study was conducted using a five-point Likert Scale questionnaire with 22 items and distributed via Google Forms to 75 UiTM undergraduates. Results indicate that peer support is vital in learner-to-learner interaction and connectedness in online learning. Next, the instructor's teaching style, choice, and use of online platforms are critical in fostering engagement. Meanwhile, course content overview, ease of content, and activities are essential for openness in online learning or learner-to-content interaction. Significant implications of the study include the need to incorporate more collaborative learning, the importance of identifying effective online teaching strategies, and ensuring more suitable, inclusive, and accessible content for ESL learners.